Allopurinol and risk of benign prostatic hyperplasia in a Finnish population-based cohort. Issue 3 (September 2018) - Kukko, Ville; Kaipia, Antti; Talala, Kirsi; Taari, Kimmo; Tammela, Teuvo; Auvinen, Anssi; Murtola, Teemu
Abstract Background Metabolic syndrome and obesity are linked with hyperuricemia, and it has also been proposed that oxidative stress associated with hyperuricemia may promote benign prostatic hyperplasia (BPH). However, it is currently unknown whether use of antihyperuricemic medication is associated with risk of developing BPH. We studied the association between BPH and use of antihyperuricemic allopurinol in a Finnish population-based cohort. Methods The study cohort consisted of 74, 754 men originally identified for the Finnish Randomized Study of Screening for Prostate Cancer (FinRSPC). Information on gout and BPH medication usage (5α-reductase inhibitors, 5ARIs) during 1996–2014 was obtained from the National medication reimbursement database. Information on BPH diagnoses from in- and outpatient hospital visits and BPH-related surgery was obtained from the National Health Care Registry. Men with a record of BPH at baseline was excluded. We used Cox regression to analyze risk of starting BPH medication, having a recorded diagnosis or undergoing BPH surgery by allopurinol use with adjustment for age and simultaneous use of statins, antidiabetic or antihypertensive drugs and aspirin or other NSAIDs. Medication use was analyzed as a time-dependent variable to minimize immortal time bias. Results Men using allopurinol had a decreased risk for all three BPH endpoints: BPH medication (HR 0.81; 95% CI 0.75–0.88), BPH diagnosis (HR 0.78; 95% CI 0.71–0.86) and BPH-related surgery (HR 0.67; 95% CI 0.58–0.76) after multivariable adjustment. The risk association did not change by cumulative use. The risk decrease disappeared after 1–2 years lag time. Only BMI modified the risk association; the risk decrease was observed only among men with BMI above the median (27.3 kg/m2 );p for interaction <0.05 for each endpoint. Conclusions We found that allopurinol use is associated with lowered risk of BPH medication, diagnosis and surgery. A possible explanation could be antioxidative effects of urate-lowering allopurinol.